Pre-contractual liability for breach of the preliminary talks - Parraguez Ruiz, Luis S. (Iuris Dictio, 2015)
Based on the standard of good faith, it is preached that the pre-contractual stage imposes a number of duties of different nature which violation gives rise to civil liability. The Ecuadorian Civil Code does not provide this category of duties and has limited the requirement of good faith to the execution phase of the contract. However, there are reasons to hold the existence of this responsibility in the national system. If that is accepted, the question to be resolved is the nature of the liability. On this point, the doctrine offers different thesis and the prevailing view that this is a type of tort. Articles 2214 and following of the Civil Code support this hypothesis in national law.